PANDANGAN MUI LAMPUNG TENTANG PERKAWINAN PENDERITA THALASSEMIA DALAM HUKUM KELUARGA ISLAM - Yunita Ramadhani; Yusuf Baihaqi; Kartika S (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study examines the perspective of the Indonesian Ulema Council (MUI) of Lampung Province on marriage involving individuals who suffer from or carry the genetic trait of thalassemia within the framework of Islamic Family Law. Using a qualitative approach with primary data from in-depth interviews with MUI Lampung informants, the findings show that MUI addresses thalassemia through the framework of Maqashid al-Shari’ah, particularly the protection of life and lineage. Premarital health screening is considered essential as a preventive effort to avoid physical disabilities and potential harm in the future. Legally, marriage between individuals with thalassemia is considered valid if the pillars and conditions of marriage are fulfilled; however, substantively, MUI emphasizes that such marriages may become makruh (discouraged) or even haram (prohibited) if medical evidence indicates a high risk of having children with thalassemia major, reflecting the principle of preventing harm (sadd al-dhari’ah). MUI also highlights the importance of honesty regarding health conditions between prospective partners and offers solutions such as reproductive risk management, including the option of not having biological children for the sake of public welfare (maslahah), ultimately demonstrating an integration of normative Islamic law with medical and social approaches in modern Indonesian family law.